2013
DOI: 10.1038/srep02027
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Meta-Analysis of Functional Imaging Studies of Social Rejection

Abstract: Early neuroimaging studies using Cyberball suggested that social rejection activated the pain matrix, as identified in studies of physical pain. However, these early studies were characterized by small sample sizes. Our statistical multi-level kernel density analysis (MKDA) of Cyberball neuroimaging studies with 244 participants fails to support the claim that social rejection operates on the same pain matrix as nociceptive stimuli, questioning whether social pain is more figurative or literal. We also perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
201
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 23 publications
17
201
1
2
Order By: Relevance
“…In line, a recent meta-analysis suggested that activation in these regions during social exclusion might be related with enhanced social uncertainty, social distress, and social rumination [15]. Activation in the dorsal ACC/mPFC and Insula have been related to self-reported distress during exclusion in the Cyberball game, however, not all studies found dorsal ACC/mPFC responsivity to social exclusion [14,15,19,20], or only found it in the first trials of the exclusion game [11]. Furthermore, studies investigating adolescents and children found ventral ACC/mPFC responses to distress during social exclusion [11,[21][22][23].…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…In line, a recent meta-analysis suggested that activation in these regions during social exclusion might be related with enhanced social uncertainty, social distress, and social rumination [15]. Activation in the dorsal ACC/mPFC and Insula have been related to self-reported distress during exclusion in the Cyberball game, however, not all studies found dorsal ACC/mPFC responsivity to social exclusion [14,15,19,20], or only found it in the first trials of the exclusion game [11]. Furthermore, studies investigating adolescents and children found ventral ACC/mPFC responses to distress during social exclusion [11,[21][22][23].…”
Section: Introductionmentioning
confidence: 64%
“…The ACC and mPFC are vital for expectancy-violation, error-detection, the processing of cognitive conflict, and self-and other referential processing [16][17][18]. In line, a recent meta-analysis suggested that activation in these regions during social exclusion might be related with enhanced social uncertainty, social distress, and social rumination [15]. Activation in the dorsal ACC/mPFC and Insula have been related to self-reported distress during exclusion in the Cyberball game, however, not all studies found dorsal ACC/mPFC responsivity to social exclusion [14,15,19,20], or only found it in the first trials of the exclusion game [11].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although the experiments included in the metaanalysis model would not be completely comparable or coherent with each other, the process of the meta-analysis is effective to reduce the statistical idiosyncrasies possibly embedded in individual experiments and to produce statistically reliable and valid outcomes (e.g., common activation foci, common neural correlates of a function of interest) (Wager et al 2004;Etkin and Wager 2007;Costafreda 2009). Of course, the meta-analysis is also the most feasible method to increase the statistical power, which is likely to be week in each individual neuroimaging study due to its small sample size (Cacioppo et al 2013). Scholars who are interested in neuroimaging studies of moral virtue and character can utilize this analysis method once multiple neuroimaging experiments, which might seem to be primarily incomparable, are conducted.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%